2019
DOI: 10.1111/jeb.13534
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect effects of sexual signal loss on female reproduction in the Pacific field cricket (Teleogryllus oceanicus)

Abstract: Sexual signal evolution may present fitness consequences for the non‐signaling sex due to shared genes and altered social conditions, but this is rarely studied in natural populations. On the Hawaiian Island of Kauai, most male Teleogryllus oceanicus (Pacific field crickets) lack the ability to sing because of a novel wing mutation (flatwing) that arose and spread in <20 generations. Obligately silent flatwing males have been highly successful because they avoid detection by a deadly, acoustically‐orienting pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 69 publications
1
15
1
Order By: Relevance
“…We analysed previously published RNA-seq data collected from pure-breeding normal-wing and flatwing cricket lines across a range of tissues: neural tissue at 7 days post-adulthood ( n = 48 libraries, 6 replicates per sex × genotype) [ 23 ]; neural, thoracic and gonad tissue at ca 14 days post-adulthood ( n = 36 libraries, 3 replicates per tissue × sex × genotype) [ 24 ]; and developing wingbuds ( n = 12 libraries, 3 replicates per sex × genotype) [ 27 ]. All cricket populations used in the above studies were derived from a single sample of a wild population in Wailua, Kauai ([ 25 ], electronic supplementary material). All males were hemizygous for their respective morph genotype ( flatwing versus normal-wing ), while females were homozygous.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We analysed previously published RNA-seq data collected from pure-breeding normal-wing and flatwing cricket lines across a range of tissues: neural tissue at 7 days post-adulthood ( n = 48 libraries, 6 replicates per sex × genotype) [ 23 ]; neural, thoracic and gonad tissue at ca 14 days post-adulthood ( n = 36 libraries, 3 replicates per tissue × sex × genotype) [ 24 ]; and developing wingbuds ( n = 12 libraries, 3 replicates per sex × genotype) [ 27 ]. All cricket populations used in the above studies were derived from a single sample of a wild population in Wailua, Kauai ([ 25 ], electronic supplementary material). All males were hemizygous for their respective morph genotype ( flatwing versus normal-wing ), while females were homozygous.…”
Section: Methodsmentioning
confidence: 99%
“…One might therefore expect flatwing to have little if any effect on female gene expression or associated phenotypes; however, this does not appear to be the case. Recent reports indicate that the flatwing mutation has pleiotropic or otherwise linked consequences for female gene expression [23], and for female life-history traits (reduced reproductive investment, increased rate of mating failure, increased somatic mass index, growth rate) [24][25][26]. While there is therefore evidence that flatwing has sexually antagonistic fitness effects in at least some contexts, such as reproductive investment, we can confidently infer only that it is under strong sex-biased selection, providing considerable fitness benefits to males via sex-limited phenotypic effects on wing morphology (Zuk et al [22] found < 1% of flatwing males harboured lethal endoparasitic larvae, versus > 30% of normal-wing males).…”
Section: Introductionmentioning
confidence: 99%
“…Prior work has shown that male quality has a greater impact on offspring viability than genetic interactions between T. oceanicus parents [34], and homozygous flatwing and normal-wing females do not produce different numbers of offspring when mated with a flatwing male [35]. We thus believe that an outcrossing advantage is unlikely to explain our results.…”
Section: Discussionmentioning
confidence: 55%
“…Though we controlled for differences in attractiveness mediated by courtship song, the morphs express different cuticular hydrocarbons [11], olfactory signals used in sexual communication, though it is unclear whether they differ in attractiveness [33]. Prior work has shown that male quality has a greater impact on offspring viability than genetic interactions between T. oceanicus parents [34], and homozygous flatwing and normal-wing females do not produce different numbers of offspring when mated with a flatwing male [35]. We thus believe that an outcrossing advantage is unlikely to explain our results.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is still unclear whether the changes in transcriptional regulation observed in the Kauai population represent adaptive changes in immunity and resistance to being parasitized by O. ochracea, or whether some changes might in fact be induced by the parasitoids themselves, which have coevolved with Kauai crickets and may therefore have acquired counter-defenses. Although flatwing males do not seem to differ from their normal-wing counterparts in our measures of immunity (Bailey et al, 2011, this study), a recent study found that flatwing males produce significantly more offspring per individual mating than do normal-wing males (Heinen Kay et al, 2019). Traits such as fitness and immunity undoubtedly affect transcription of large numbers of genes relating to wing and/ or testis development, among other functions (Rayner et al, 2019).…”
Section: F I G U R Ementioning
confidence: 67%